Perubahan Pola Hidup Guru Pendidikan Jasmani Selama Pandemi Covid-19 - Kusuma, Angga Indra; Pieter, Shandy; Puriana, Ramadhany Hanato; BP, Ismawandi; Utamayasa, I Gede Dharma (Universitas Hamzanwadi, 2022)
The Covid-19 pandemic has caused the government to take Lock Down, PSBB, New Era, PPKM policies. This policy resulted in schools and public places being closed or reduced mobility. This can trigger changes in lifestyle and physical activity for physical education teachers. The purpose of this study is to describe and analyze changes in lifestyle and physical activity of physical education teachers before and during the pandemic. The research method was carried out with quantitative descriptive where in data collection using a questionnaire with the help of the google form platform. The research subjects were 100 physical education teachers (aged 24-53 years, 29% female). The results of this study are that there are changes in the exercise performed, the frequency and duration of exercise tend to decrease, the frequency of eating tends to be the same, and the duration of sleep tends to decrease. The conclusion of the research is that there are changes in lifestyle and physical activity for physical education teachers during the pandemic. Suggestions for physical education teachers can rearrange lifestyle and physical activity so that they can increase immunity as one of the prevention of covid 19 transmission.